Elementary School Teacher's Competence in Implementing Differentiated Learning in Surakarta City - Siti Istiyati; Supianto; Sri Marmoah; Jenny Indrastoeti Siti Poerwanti; Sukarno (Postgraduate, University of Mataram, 2024)
In elementary schools, differentiated learning is crucial as this phase is a critical period for establishing fundamental learning and child development. Differentiated learning aims not only to improve academic outcomes but also to develop students' social and emotional skills. The findings are expected to offer concrete recommendations for developing more effective teacher training programs and educational policies that support differentiated learning, enhancing education quality and student learning outcomes in elementary schools. This study evaluates elementary school teachers' competencies in implementing differentiated learning in Surakarta. A survey research design was used to collect data on teachers' abilities to plan, implement, and evaluate differentiated learning. Using a quantitative approach, the study involved 214 teachers randomly selected from various elementary schools in Surakarta. The distributed questionnaire collected data on knowledge, skills, and differentiated learning practices. The collected data were analyzed using descriptive statistical analysis with SPSS software. The results reveal variation in teacher competencies, with strengths primarily in using differentiated learning media and practice reflection, while the greatest challenges are in assessing student learning progress and implementing strategies. These findings highlight the need for additional training and support to enhance the effectiveness of differentiated learning implementation in elementary schools.